KETERGANTUNGAN PETANI SAYURAN TERHADAP TENGKULAK SEBAGAI PATRON-KLIEN DALAM KEGIATAN PERTANIAN (STUDI KASUS DESA WAKULI KECAMATAN KAPONTORI KABUPATEN BUTON) - Eva Hardian; La Ode Alwi; Hidrawati (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The income of vegetable farmers in Wakuli Village comes from production results and the prices received by farmers. Efficient management and increased production should have an impact on farmer welfare. However, in reality the exchange rate and the existence of farmers are often neglected in the economic system, especially in the distribution system for vegetable crops, so they are unable to provide positive profits. The aim of this research is to analyze the role of middlemen from the perspective of vegetable farmers and to determine the type of dependency of vegetable farmers as patron-clients. The informants in this research consisted of 1 key informant from village officials, the main informant consisted of 7 vegetable farmers and 3 middlemen, as well as 1 supporting informant from the head of the farmer group. The data collection techniques used in this research are observation, interviews and documentation. The instruments in this research were an interview guide, writing tools and recording equipment. Data analysis uses the Miles and Huberman interactive data analysis model. The research results show that middlemen in agricultural activities in Wakuli Village have an active role as capital owners, buyers and marketers. There are several types of middleman roles that are considered to be able to help farmers in dealing with economic and social problems. The role of the middleman covers all aspects (production, marketing, financial and social) needed by farmers in Wakuli Village. In the vegetable production process, farmers depend on capital provided by middlemen and in the marketing process the vegetables are sold to middlemen. Of all the farmers who were informants in this research, on average, they channeled their vegetable harvests to middlemen.